2020
DOI: 10.1055/s-0040-1712993
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Differentiation of Benign and Malignant Non-epithelial Ovarian Tumors: Clinical Features and Tumor Markers

Abstract: Objective To evaluate the role of clinical features and preoperative measurement of cancer antigen 125 (CA125), human epididymis protein (HE4), and carcinoembryonic antigen (CEA) serum levels in women with benign and malignant non-epithelial ovarian tumors. Methods One hundred and nineteen consecutive women with germ cell, sex cord-stromal, and ovarian leiomyomas were included in this study. The preoperative levels of biomarkers were measured, and then surgery and histopathological analysis were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…In contrast, the study under discussion here, 90% of the non-epithelial ovarian cancer patients studied exhibited a unilateral ovarian tumor as their primary site, which agreement with 91% reported by In the current study, it was found that 54% of the patients were in a pre-menopausal state. This approximates the findings in the study by Gomes et al (2020) where pre-menopausal patients constituted 57% of the sample.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In contrast, the study under discussion here, 90% of the non-epithelial ovarian cancer patients studied exhibited a unilateral ovarian tumor as their primary site, which agreement with 91% reported by In the current study, it was found that 54% of the patients were in a pre-menopausal state. This approximates the findings in the study by Gomes et al (2020) where pre-menopausal patients constituted 57% of the sample.…”
Section: Discussionsupporting
confidence: 88%
“…The most prevalent histological subtype of ovarian sex cord-stromal tumors (OSCTs) was adult granulosa cells, constituting approximately 72% of cases in this study. This observation is in line with the study conducted by Gomes et al (2020) who reported a similar distribution, with adult granulosa cell tumors representing around 71% of OSCT cases.…”
Section: Figure 4: Kaplan-meier Curve Showing Statisticall Significan...supporting
confidence: 92%
See 1 more Smart Citation
“…Carcinoembryonic antigen (CEA) is present in endoderm-derived digestive system cancer and normal digestive tract tissues, and also present in a trace amount in normal human serum, which can be used as a diagnostic marker for breast cancer, lung cancer, and colorectal cancer, but its specificity and sensitivity are not high (4). Carbohydrate antigen 125 (CA125), a glycoprotein that can be bound by the monoclonal antibody OC125, is most commonly found in the serum of patients with epithelial ovarian tumors, but does not exist in normal ovarian tissues, which has high diagnostic sensitivity, but low specificity (5). Neuron-specific enolase (NSE) is an acid protease unique to neuroendocrine cells and neurons, which is a specific marker for neuroendocrine tumors such as medullary thyroid carcinoma and small cell carcinoma (6).…”
Section: Introductionmentioning
confidence: 99%
“…Human epididymis protein 4 (HE4) is a protein that was first shown to be secreted from distal epithelial cells of human epididymal ducts 8 . It is known that there is a relationship between the serum levels of the HE4 protein, which is a protease inhibitor, and many malignancies, especially of ovarian origin 9–12 . It is also known that this protein has roles in regulation of cell migration, adhesion, and invasion, and in autoimmune diseases 13,14 .…”
Section: Introductionmentioning
confidence: 99%